2021
DOI: 10.3390/ijerph18137037
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of SARS-CoV-2 Detection by Rapid Antigen and by Three Commercial RT-qPCR Tests: A Study from Martin University Hospital in Slovakia

Abstract: The global pandemic of coronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is having a tremendous impact on the global economy, health care systems and the lives of almost all people in the world. The Central European country of Slovakia reached one of the highest daily mortality rates per 100,000 inhabitants in the first 3 months of 2021, despite implementing strong prophylactic measures, lockdowns and repeated nationwide antigen testing. The present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 50 publications
(61 reference statements)
0
8
0
Order By: Relevance
“…Nidovirals, such as SARS-CoV-2, use discontinuous transcription of parts of their positive-sense RNA genomes to create a nested set of negative-sense sgRNAs that, in turn, serve as templates for transcription of mRNAs to encode virus structural and accessory proteins [ 10 , 42 ]. Assays available for detection of SARS-CoV-2 nucleic acids predominantly target genomic nucleic acids in either single or multiplex formats [ 15 , 17 , 18 , 21 , 44 , 45 , 46 ]. The main limitation of specifically detecting sgRNAs by RT-qPCR is unintended amplification of other shorter sgRNAs generated in the series of discontinuous transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…Nidovirals, such as SARS-CoV-2, use discontinuous transcription of parts of their positive-sense RNA genomes to create a nested set of negative-sense sgRNAs that, in turn, serve as templates for transcription of mRNAs to encode virus structural and accessory proteins [ 10 , 42 ]. Assays available for detection of SARS-CoV-2 nucleic acids predominantly target genomic nucleic acids in either single or multiplex formats [ 15 , 17 , 18 , 21 , 44 , 45 , 46 ]. The main limitation of specifically detecting sgRNAs by RT-qPCR is unintended amplification of other shorter sgRNAs generated in the series of discontinuous transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…However, 2 studies with IFU-conforming testing procedure on NP or AN/MT sample, still showed a low sensitivity. This quite likely results from the on average low viral load in 1 study [49], and the asymptomatic study population in the other [175]. On the contrary, compared to the other studies unusual high sensitivity was found in studies where average viral load was high [45, 84, 144, 145] or participants were mainly within the first week of symptom onset [42, 54, 135].…”
Section: Discussionmentioning
confidence: 97%
“…Rapid and accurate diagnosis is crucial for successful outbreak containment. During the current COVID-19 public health emergency, the gold standard for the diagnosis of COVID-19 infection is the detection of viral RNA ( 14 , 15 ). Using homogeneous reaction through plasma technology, we developed a new virus preservation solution, focusing on the selection of high-efficiency anticoagulants, natural preservatives, low-toxicity cell membrane protectors, and osmotic pressure stabilizers.…”
Section: Discussionmentioning
confidence: 99%
“…This result further showed that viruses treated with our virus preservation solution had intact virus particles, making it easier to extract the nucleic acid of low copy number viruses and reducing false negatives. B (14,15). Using homogeneous reaction through plasma technology, we developed a new virus preservation solution, focusing on the selection of high-efficiency anticoagulants, natural preservatives, low-toxicity cell membrane protectors, and osmotic pressure stabilizers.…”
Section: Integrity Of Viral Proteinsmentioning
confidence: 99%